Pengaruh Keterampilan, Potensi dan Relasi Sosial Usaha Penjahit Pakaian (Taylor) terhadap Peningkatan Pendapatan Keluarga di Kecamatan Nita - Maria Alfonsa; Wilhelmina Mitan; Siktania Maria Diliana (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of skills, potential and social relations in the clothing tailoring business (Taylor) on increasing family income in Nita District. This research uses an associative approach with a form of causal relationship and uses a quantitative approach. The population and sample used in this research were clothing tailor business owners in Nita District. The data collection technique used a questionnaire distributed to every tailor in Nita District, a total of 30 respondents, where data analysis used multiple linear regression using the Statistical Package for the Social Sciences (SPSS). The results of this research show that partially skills have no effect on increasing family income, potential has an effect on increasing family income and social relations have no effect on increasing family income, and simultaneously potential skills and social relations have an effect on increasing family income.